2002
DOI: 10.1007/s00464-001-9193-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increased intraabdominal pressure on colonic anastomoses

Abstract: An IAP increased to 20 mmHg and higher was found to result in impaired strength and wound healing in colocolic anastomoses, as reflected by the decreased bursting pressure and mucosal layer formation, and by the increased inflammation at the anastomosis sites of animals subjected to high IAP values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 15 publications
(20 reference statements)
1
35
1
Order By: Relevance
“…Ischemia of splanchnic organs, including the intestine during P, and their subsequent and sometimes paradoxically increased [7] reperfusion after P can cause I/R injury [1][2][3][4][5][6][7][8][9]. P-associated intestinal I/R injury has important implications, as reflected by clinical reports of lethal intestinal ischemia after laparoscopy and our report concerning the decreased strength and healing of colocolic anastomoses in rats after high-pressure P [9,10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ischemia of splanchnic organs, including the intestine during P, and their subsequent and sometimes paradoxically increased [7] reperfusion after P can cause I/R injury [1][2][3][4][5][6][7][8][9]. P-associated intestinal I/R injury has important implications, as reflected by clinical reports of lethal intestinal ischemia after laparoscopy and our report concerning the decreased strength and healing of colocolic anastomoses in rats after high-pressure P [9,10].…”
Section: Discussionmentioning
confidence: 98%
“…I/R injury is responsible for most of the damage complicating reversible arterial insufficiency of the intestine, provided there is no venous congestion [5][6][7][8]. I/R injury impairs anastomotic healing in the bowel and is the most likely mechanism of the detrimental effect of the high IAPs on colonic anastomoses reported originally by our group [9][10][11]. Intestinal I/R injury leads to "oxidative stress", which propagates further injury [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[62,68] I/R injury impairs anastomotic healing in the bowel and is the most likely mechanism of the detrimental effect of the high IPPs on colonic anastomoses reported. [69,70] Intestinal I/R injury leads to oxidative stress, which propagates further injury. Pressure-induced I/R injury in the intestine is reflected by the increased oxidative enzyme activity and oxidant generation of intestinal tissue after pressure.…”
Section: Intraperitoneal Pressure (Ipp)mentioning
confidence: 99%
“…[68,73] Pressure-associated intestinal I/R injury has important implications, as reflected by clinical reports of lethal intestinal ischemia after laparoscopy and with the reports demonstrating the decreased strength and healing of colocolonic anastomoses in rats after a high-pressure procedure. [69,70] The relation between intestinal I/R injury and oxidative stress was further characterized by Takada et al, who reported that intestine subjected to mesenteric artery occlusion followed by reperfusion, developed mucosal damage that is correlated with increased local production of NO and metabolites, nonselective inhibitor of NOS, L-NAME. [72] The intestine acts as a barrier to the luminal contents, which include bacteria and the endotoxins.…”
Section: Intraperitoneal Pressure (Ipp)mentioning
confidence: 99%
“…Several studies have investigated the effects of increased intra-abdominal pressure on the cardiovascular and respiratory systems, the renal system, liver and abdominal wall4. Some studies have reported the effects of pneumoperitoneum on the healing of intestinal injury and anastomosis5, 6. Very few studies, however, have investigated the effects of pneumoperitoneum on the healing process of other abdominal organs, especially the stomach.…”
Section: Introductionmentioning
confidence: 99%